Smallwood Interview 10A - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
Robert Pitt interviews Joseph (Joey) Smallwood. Mr. Smallwood recalls the great diffculty of Depression years in Newfoundland and the riot of 1932, which began with a march on the Colonial Building, where the premier, Richard Squires was trapped. Very difficult to hear Robert Pitt ask Mr. Smallwood questions. Smallwood Interview #10B has better audio recording of both parties for this interview.